The Comparative Analysis of Academic Missions Abroad of Teachers and Graduates of Russian Ecclesiastical Academies and Universities (1869-1917) - Lesaev Ruslan (Вестник Православного Свято-Тихоновского гуманитарного университета: Серия ИИ. История, история Русской Православной Церкви)
The article is devoted to the comparative analysis of academic missions abroad of teachers and graduates of Russian ecclesiastical academies and universities. For the first time the author studies the role of scientific visits abroad in the development of Russian science of the XIX-th — the beginning of XX-th centuries. He compares the academic missions and classifies them according their motivation and purpose; organization and the registration of an office work; sponsorship, rights and duties of travelers; geographical directions and results.